New Mussel Inspired Polydopamine-Like Silica-Based Material for Dye Adsorption - Massaro, Marina (Nanomaterials (Basel), 2020)
A straightforward and economic procedure has been developed for the synthesis of a new polydopamine-like silica-based material that has been obtained by oxidation of catechol with KIO(4) followed by reaction with 3-aminopropyltrimethoxysilane. All techniques adopted for characterization showed that the obtained material is rich in different functional groups and the morphological analyses revealed dimensions in the nanometric range. The hybrid material has been characterized by several techniques showing its polydopamine-like nature, and preliminary observations for dye adsorption have been reported.